Photoluminescence properties of Sm2+-doped BaBr2 under hydrostatic pressure - Wiegand, Marie Christin; Sievers, Werner; Lindner, Jörg; Tröster, Th.; Schweizer, S. (Journal of Luminescence)
Photoluminescence spectra of Sm^(2+)-doped BaBr^2 have been measured under hydrostatic pressures up to 17 GPa at room temperature. In the low pressure range a red-shift of the broad 5d–4f transition of -145 cm^(-1)/GPa is observed. From 5 to 8 GPa a phase mixtureof the initial orthorhombic phase and the high-pressure monoclinic phase gives rise to two 5d–4f bands, which are strongly overlapping. Above 8 GPa the crystalis completely transformed to its high-pressure phase where two different Sm2^(2+) sites exist, but only one broad 5d–4f transition is detected. It exhibits are d-shift of -36 cm^(-1)/GPa. In addition,the line shifts of the (_^5)D_0→(_^7)F_J (J=0,1,2) transitions are investigated. Linear shifts of -19cm^(-1)/GPa for J=0,2 and of -13cm^(-1)/GPa for J01 are observed in the pressure range from 0 to 5 GPa.